Suppression of corrosion processes at the nickel surface employing immobilized container structures based on transition metal oxides - Logvinovich, Aliaksandr S.; Sviridova, Tatsiana V.; Agabekov, Vladimir E.; Sviridov, Dmitri V. (Journal of the Belarusian State University. Chemistry, 2017)
It is shown that thin films of the hydrated molybdenum oxide grown at the nickel surface employing sonoinduced polycondensation of molybdic acid can behave as the container structures occluding benzotriazole (corrosion inhibitor). The resultant films demonstrate good corrosion protection properties and impart enhanced wear resistance of nickel surface reducing the wear rate 5-fold due to preventing the tribocorrosion.